(untitled) - Thewlis, Stephen (Pacific Grove, 1997)
This four-level series systematically addresses the form, meaning and use of each structure. It focusese learners' attention on the greatest challenge for each structure to help them communicate accurately, meaningfully, and appropriately.
Keywords: English language,English language; Grammar